Effect of promising rice (Oryza sativa L.) varieties and nutrient management practices on growth, development and crop productivity in eastern Himalayas - M.N., Harish; Choudhary, Anil K.; Singh, Y.V.; Pooniya, Vijay; Das, Anup; T., Varatharajan; Babu, Subhash (Annals of Agricultural Research, 2018)
A field experiment was conducted at the Experimental Farm of ICAR-Research Complex for North Eastern Hill Region, Barapani, Meghalaya during Kharif 2016 to study the effect of promising rice varieties and nutrient management practices on plant growth, development, and grain and biological yield of lowland rice in Eastern Himalayas. The experiment was laid-out in split-plot design replicated thrice consisting of 12 treatment combinations viz. 4 nutrient management practices [100% organic, 100% inorganic (RDF), INM (50% RDF through fertilizers + remaining 50% RDF through FYM and rock phosphate), and absolute control] in main-plot, and 3 promising rice varieties [Shahsarang-1, Lumpnah and Megha semi-aromatic-2] in sub-plots. The results showed that the plant height, dry matter accumulation (DMA), leaf area index (LAI), growth indices like absolute growth rate (AGR), crop growth rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR) improved constantly with the succession of crop growth period i.e. 30 to 90 days after transplanting (DAT) as well as at harvest. Plant height, DMA, LAI, and growth indices in rice crop were observed to be considerably influenced by different nutrient management practices. Among different nutrient management practices, significantly higher magnitude of above parameters was found in integrated nutrient management (INM) practice followed by inorganic practice, organic practice and control, respectively. Among rice varieties, Shahsarang-1 exhibited higher magnitude of above growth parameters followed by Lumpnah and Megha SA2, respectively. These rice varieties both under INM as well as under inorganic practice gave higher amount of growth parameters viz. plant height, DMA, LAI, growth indices in rice greater than their other counterparts. Grain yield was significantly higher (4.18 t ha–1) in INM practice followed by inorganic, organic and control treatment. The trend of grain yield was INM>inorganic>organic>control treatment, respectively. Similar trend was also observed for biological yield. Among rice varieties, Shahsarang-1 produced significantly highest grain yield (3.86 t ha–1) followed by Lumpnah (3.60 t ha–1) and Megha SA2 (3.19 t ha–1), respectively. Similar trend was also observed for biological yield. In nutshell, INM practice (50% RDF through fertilizers + remaining 50% RDF through FYM and rock phosphate) is the best nutrient management technology to harness better growth and crop productivity in eastern Himalayas. Similarly, Shahsarang-1 was the best performer in terms of growth and crop productivity over other two promising rice varieties viz. Lumpnah and Megha SA2 in north-eastern Himalayan region.